2003
DOI: 10.1016/s0167-4889(02)00399-3
|View full text |Cite
|
Sign up to set email alerts
|

The novel retinoid AHPN/CD437 induces a rapid but incomplete apoptotic response in human myeloma cells

Abstract: The synthetic retinoid 6-[3-(1-adamantyl)-4-hydroxyphenyl]-2-naphthalene carboxylic acid (AHPN/CD437) appears to possess an apoptotic activity superior to classical retinoids in vitro as in vivo. Numerous studies have shown that CD437-induced apoptosis is independent of its nuclear receptor activity, suggesting that CD437 might have a unique mechanism of action. The purpose of this study was to compare CD437- and all-trans retinoic acid (atRA)-induced cell death. CD437 provoked a rapid apoptotic phenotype imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…These results were consistent with previous investigations showing that ATRA treatment induced potent inhibition on OPM-2 MM cell growth, 44,45 but no significant effects on U266 and L363 cells, which were detected as RAR␣2 Ϫ cells in our study. 46 Based on these observations, we conclude that RAR␣2 expression played a crucial role in mediating ATRAinduced MM cell death and growth inhibition.In this study, we found that RAR␣2 expression was highly related to poor prognosis in TT2 and TT3 clinical trials. Nonetheless, our previous investigation reported 70 high-risk genes in MM in which RAR␣2 was not included.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…These results were consistent with previous investigations showing that ATRA treatment induced potent inhibition on OPM-2 MM cell growth, 44,45 but no significant effects on U266 and L363 cells, which were detected as RAR␣2 Ϫ cells in our study. 46 Based on these observations, we conclude that RAR␣2 expression played a crucial role in mediating ATRAinduced MM cell death and growth inhibition.In this study, we found that RAR␣2 expression was highly related to poor prognosis in TT2 and TT3 clinical trials. Nonetheless, our previous investigation reported 70 high-risk genes in MM in which RAR␣2 was not included.…”
mentioning
confidence: 67%
“…These results were consistent with previous investigations showing that ATRA treatment induced potent inhibition on OPM-2 MM cell growth, 44,45 but no significant effects on U266 and L363 cells, which were detected as RAR␣2 Ϫ cells in our study. 46 Based on these observations, we conclude that RAR␣2 expression played a crucial role in mediating ATRAinduced MM cell death and growth inhibition.…”
mentioning
confidence: 67%
“…Preclinical development In vitro and in vivo, in different models of Synthetic retinoid (triterpenoid) able to promote human tumors. [73][74][75] MOMP independently from nuclear receptors. [76][77][78] CDDO Phase I clinical trials Metastatic or unresectable solid tumors Synthetic retinoid (triterpenoid), induces and lymphoma MOMP in isolated mitochondria.…”
Section: Cd437mentioning
confidence: 99%
“…Moreover, the treatment of human malignant melanoma with combined p53 vector plus antisense cyclin D1 has been observed to lead to enhanced growth-suppressive and apoptotic effects as compared with either therapy alone [173]. In this matter, it has also been reported that diverse anticancer drugs, including Mimeault/Bonenfant/Batra doxorubicin, vinblastine, paclitaxel, cytosine arabinoside, betulinic acid and the synthetic retinoid 6-[3-(1-adamantyl)-4-hydroxyphenyl]-2-naphthalene carboxylic acid (CD437), are able to induce apoptotic death of melanoma cells via a mitochondrion-dependent pathway leading to the activation of caspases [166,183]. This suggests that the compounds which are able to alter mitochondrial functions could represent interesting adjuvant antitumoral agents against metastatic melanoma forms.…”
Section: Combination Therapiesmentioning
confidence: 99%